Motivation Program to Reduce Occupational Accidents in a Manufacturing Company - Santillan Mercado, Milagros (2024)
the purpose of this research study was to determine whether implementing a motivation program could lead to a reduction in the rate of occupational accidents in the bakery plant of a manufacturing company based in Lima. The study followed a quasi-experimental approach and used a pretest/posttest design with a single group and a sample of 117 workers. The data collection methods included statistical data on work-related accidents, direct observations in the workplace, recording and monitoring of interactions, and a motivation questionnaire. The research results revealed that implementing the IPLEFOR motivation program—which spanned 21 months—led to a 100% reduction in the accident rate. Consequently, it led to a significant improvement in the occupational health and safety system.